James Joyce’s Ulysses in Ricardo Piglia’s Respiración artificial - Elgue-Martini, Cristina (ABEI Journal, 2014)
The aim of this article is to analyse the presence of James Joyce’s Ulysses (1922) in Respiración artificial, the first novel by the Argentinean writer Ricardo Piglia (1941- ). Published in 1980, Respiración is a fictional representation of a near and tragic past, the last Military Dictatorship in Argentina, but it is also a literary re-assessment of earlier stages in the history of the nation, as well as a metatextual comment on western culture and on Argentine literature. James Joyce’s Ulysses is present in Piglia’s novel mainly through its main character, Emilio Renzi, who belongs to a literary genealogy that can be traced back to Stephen Dedalus and even Stephen Daedalus, the protagonist of Stephen Hero. The analysis will focus on the many allusions andquotations of Ulysses in Piglia’s novel with the purpose of showing how they are resignified by Piglia in a different sociocultural context.Keywords: Ulysses; Respiración artificial; Stephen Dedalus; Emilio Renzi; historiographic metafiction.